The Effect of Aqueous Extract of Ocimum gratissium (Linn) on 1, 2 - Dimethyl Hydrazine induced Colon Cancer in Male Wistar Rats - Umeaku Ugochukwu; A. Ofusori David; P. Umeaku Obioma; A. Edward Tolulope (International Journal of Human Anatomy, 2020)
Background Colon cancer is one of the leading causes of cancer death world-wide. There is a steady increase in incidence over the past four decades in developing countries. This has been partly attributed to increasingly low intake of vegetables among other causes. Aims Therefore this study aims to evaluate the protective effect of aqueous extract of Ocimumgratissimum (OG) leaves (a staple vegetable) on experimental model of colon carcinogenesis induced with 1, 2 Dimethylhydrazine (DMH). This is compared with celecoxib (a cyclooxygenase-2 inhibitor) which is used in the chemoprevention of colon cancer. Methods Sixty adult male Wistar rats were randomly divided into six groups: A to F, n=10. Group A was the normal control, Group B was given only DMH weekly for 16 weeks,Groups C, D and E were given graded doses of OG for two weeks prior to cancer induction by DMH. After which both OG and DMH were given for 16weeks. Group F received celecoxib daily for two weeks prior to cancer induction. Colonic wall was analysed grossly, histologically and biochemically. The induced lesions were staged investigated and staged using Duke’s Staging method. Results The result showed tumour incidence in groups B and C while no evidence of primary colonic tumour was observed in groups A, D, E and F. There was a dose dependent increase in the goblet cell count in the groups treated with OG with group E being statistically higher than group F. There was a significant reduction in collagen staining intensity (F = 129.74, p < 0.0001) for the colonic wall in group B when compared to other groups. There was a decreased nucleo-cytoplasmic ratio in groups C, D, E and F when compared to group B. There was a significant increase in the concentration of nitric oxide and prostaglandin E2in group B when compared to other groups D, E and F. Conclusion In conclusion, this research showed a protective effect of Ocimumgratissimum leaves on 1, 2-dimethylhydrazine-induced colon cancer which further corroborated its ethno-medicinal use.
Keywords: Ocimum gratissium